(untitled) (Texas Journal of Philology, Culture and History, 2024)
The idea of introducing new technologies to education is not new, and as a result, research on this topic has been carried out for years. However, the rate of introduction of new technologies in higher education in Uzbekistan is very slow. The purpose of this article is to propose a conceptual framework for the development of mobile learning, in particular, the introduction of mobile applications into the educational process in primary education. This goal is achieved by analyzing the existing measures and the existing foundations of mobile education, which are used to improve the quality of education through the active use of information and communication technologies. The proposed system includes three main elements: applied computing, information systems, and theory of computation. It is important that each of them is done correctly and that there is continuity between them.